2020
DOI: 10.1002/advs.201902688
|View full text |Cite
|
Sign up to set email alerts
|

Gram‐Scale Synthesis of 41% Efficient Single‐Component White‐Light‐Emissive Carbonized Polymer Dots with Hybrid Fluorescence/Phosphorescence for White Light‐Emitting Diodes

Abstract: Fluorescent carbon dots (CDs) are compelling optical emitters to construct white light‐emitting diodes (WLEDs). However, it remains a challenge to achieve large‐scale and highly efficient single‐component white‐light‐emissive CDs suitable for WLED applications. Herein, a low cost, fast processable, environmentally friendly, and one‐step synthetic approach is developed for the preparation of gram‐scale and highly efficient single‐component white‐light‐emissive carbonized polymer dots (SW‐CPDs). It is revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
84
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(87 citation statements)
references
References 36 publications
2
84
0
1
Order By: Relevance
“…These emerging luminescent nano-dots are small-sized (<10 nm), mass-producible, compatible with organic materials and optically robust. [20][21][22][23] Furthermore, the incorporation of CDs with polymers has produced a series of composite lms with reliable URTP long aerglow performance, [24][25][26][27][28][29] enriching the library of transparent and exible URTP materials. It was recently reported that CDs in polymer matrices can serve not only as URTP emitters, but also as reactive centers that alter the regional environments in the materials, facilitating dynamic URTP performance.…”
Section: Introductionmentioning
confidence: 99%
“…These emerging luminescent nano-dots are small-sized (<10 nm), mass-producible, compatible with organic materials and optically robust. [20][21][22][23] Furthermore, the incorporation of CDs with polymers has produced a series of composite lms with reliable URTP long aerglow performance, [24][25][26][27][28][29] enriching the library of transparent and exible URTP materials. It was recently reported that CDs in polymer matrices can serve not only as URTP emitters, but also as reactive centers that alter the regional environments in the materials, facilitating dynamic URTP performance.…”
Section: Introductionmentioning
confidence: 99%
“…[58] Wang et al prepared a carbonized polymer dot with dual emission of blue fluorescence and yellow-green phosphorescence, with a total PLQY of up to 41% (Figure 4a,b). [59] Recently, Wu et al prepared white light-emitting graphene QDs with a high PLQY of 34% using 1,5-diaminonaphthalene (DAN) as the precursor, trichloromethane (TCM) as the Cl source, and ethanol as the solvent, by a solvothermal molecular fusion method. This material showed excitation-dependent fluorescence emission and room temperature phosphorescence in the solid state.…”
Section: Single-component White Light-emitting Materials Based On Cdomentioning
confidence: 99%
“…The previous parts were reproduced under the terms and conditions of the CC BY License. [59] Copyright 2020, The Authors. Published by Wiley-VCH.…”
Section: White Light-emitting Materials Based On Cdots With Aggregatiomentioning
confidence: 99%
“…[ 9 ] The CPDs possess a polymer/carbon hybrid structure comprising of shells with abundant functional groups/polymer chains and carbon cores with high cross‐linking or slight graphitization. [ 10 ] Herein, CPDs were used to refer luminescent carbon nanomaterials in this review. Recently, an emerging perspective in the field of nanomaterials based nanomedicine is that wide space between novel advances and clinical translation of therapeutic nanomaterials is derived from incomplete understanding of nano‐bio interactions.…”
Section: Introductionmentioning
confidence: 99%